A participação do investimento estrangeiro na reestruturação do setor de ensino: uma análise da eficiência relativa de instituições de ensino superior privadas no Brasil - Piurcosky, Fabricio Pelloso (2020)
Merger, acquisition, and alliance events have been taking place since 2001 in the Brazilian private higher education sector. This fact has resulted in publicly held companies and the expansion of educational groups through the contribution of foreign investments. The discussion of foreign capital participation and control covers two important aspects: a possible restructuring of the Brazilian private higher education sector and a potential impact on the relative efficiency level of Brazilian higher education institutions. Therefore, the objective of this paper is to evaluate the effects of foreign capital inflow on the higher education sector. To fulfill this purpose, the study presents more than 170 merger, acquisition, or alliance events that occurred in Brazil between 2001 and 2019 and evaluates data from 55 education institutions from 6 different education groups between 2014 and 2017. The research uses secondary data from education consulting companies, stock exchanges, journals, literature, and reports from government agencies such as INEP and MEC. A restructuring of the studied sector is in progress, shown by the calculation of the Hirschman-Herfindahl index, which indicated an increase in the degree of concentration in recent years. Furthermore, a moderate concentration in the market already shows when considering only the graduation in the distance education modality. In light of the application of the DEA methodology, we analyzed variables that resulted in the relative efficiency of the institutions involved (quantitatively and qualitatively). Of the 55 institutions analyzed, seven were considered efficient from a quantitative perspective, and five were efficient from a qualitative perspective. It was also possible to attest that efficiency rates are increasing. The Tobit regression model compared and verified the effect of the efficiency levels results. The indicators considered influencing were the total number of students per total number of professors, the inflow of foreign capital, and the total number of doctors per total number of professors. In conclusion, the level of quantitative efficiency presented the highest contribution to the positive results of the level of the relative efficiency of the institutions.